2020
DOI: 10.3390/antibiotics9050254
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter, Observational Cohort Study Evaluating Third-Generation Cephalosporin Therapy for Bloodstream Infections Secondary to Enterobacter, Serratia, and Citrobacter Species

Abstract: Objectives: There is debate on whether the use of third-generation cephalosporins (3GC) increases the risk of clinical failure in bloodstream infections (BSIs) caused by chromosomally-mediated AmpC-producing Enterobacterales (CAE). This study evaluates the impact of definitive 3GC therapy versus other antibiotics on clinical outcomes in BSIs due to Enterobacter, Serratia, or Citrobacter species. Methods: This multicenter, retrospective cohort study evaluated adult hospitalized patients with BSIs secondary to E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 29 publications
5
14
1
Order By: Relevance
“…In this study, fluoroquinolones had a numerically lower rate of composite clinical failure than comparators (12.9% vs. 24%), but this difference was not statistically significant. The rates of clinical failure in our groups were lower than a similar study by Derrick et al (17.9% vs. 33.8%), which described overall treatment failure in patients with AmpC-producing Enterobacterales who received either third-generation cephalosporins or comparator therapy [25]. In addition, 90-day readmission rates were low (10.9% overall) but were numerically higher in the beta-lactam group (6.5% vs. 16.7%).…”
Section: Discussioncontrasting
confidence: 83%
“…In this study, fluoroquinolones had a numerically lower rate of composite clinical failure than comparators (12.9% vs. 24%), but this difference was not statistically significant. The rates of clinical failure in our groups were lower than a similar study by Derrick et al (17.9% vs. 33.8%), which described overall treatment failure in patients with AmpC-producing Enterobacterales who received either third-generation cephalosporins or comparator therapy [25]. In addition, 90-day readmission rates were low (10.9% overall) but were numerically higher in the beta-lactam group (6.5% vs. 16.7%).…”
Section: Discussioncontrasting
confidence: 83%
“…Previous literature demonstrated the effectiveness of cefepime in comparison to carbapenems for the treatment of BSI due to these bacteria [ 19 ]. In this Special Issue, Derrick and colleagues suggest that ceftriaxone may be a treatment option in patients with low-inoculum BSI due to Enterobacter cloacae and other CAE [ 20 ]. This is conceivable, since low-inoculum sources of GN-BSI are associated with lower mortality [ 21 , 22 ].…”
mentioning
confidence: 99%
“…This is conceivable, since low-inoculum sources of GN-BSI are associated with lower mortality [ 21 , 22 ]. This multicenter cohort study is the first to report the effectiveness of ceftriaxone for BSI due to CAE [ 20 ]. The study has major antimicrobial stewardship implications, since it allows de-escalation of antimicrobial therapy from carbapenems or cefepime to ceftriaxone in patients with uncomplicated CAE BSI secondary to urinary tract source without obstruction or central venous catheter infection after catheter removal [ 20 ].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have also shown no significant difference in clinical outcomes of bacteremia when 3GCs were used for definitive therapy compared to non-3 GC therapy (i.e. extended-spectrum penicillin antibiotics, fluoroquinolones, 4CGs, and carbapenems) (9). In addition, there is evidence that the administration of broad-spectrum antimicrobial agents may contribute to the establishment of resistance.…”
Section: Introductionmentioning
confidence: 98%